Combination of sentinel lymph node mapping and uterine frozen section examination to reduce side-specific lymphadenectomy rate in endometrial cancer: a Turkish Gynecologic Oncology Group study (TRSGO-SLN-002). Issue 7 (30th May 2020) - Altin, Duygu; Taşkın, Salih; Kahramanoglu, Ilker; Vatansever, Dogan; Tokgozoglu, Nedim; Karabük, Emine; Turan, Hasan; Takmaz, Özgüç; Naki, Mehmet Murat; Güngör, Mete; Köse, Mehmet Faruk; Ortac, Firat; et al.
Abstract : Objective: This study aimed to find out whether side-specific pelvic lymphadenectomy can be omitted without compromising diagnostic efficacy according to "reflex frozen section" analysis of the uterus in case of sentinel lymph node (SLN) mapping failure. Methods: Patients who underwent surgery for endometrial cancer with an SLN algorithm were stratified as low-risk or high-risk according to the uterine features on the final pathology reports. Two models for low-risk patients were defined to omit side-specific pelvic lymphadenectomy: strategy A included patients with endometrioid histology, grade 1–2, and <50% myometrial invasion irrespective of the tumor diameter; strategy B included all factors of strategy A with the addition of tumor diameter ≤2 cm. Theoretical side-specific pelvic lymphadenectomy rates were calculated for the two strategies, assuming side-specific pelvic lymphadenectomy was omitted if low-risk features were present on reflex uterine frozen examination, and compared with the standard National Comprehensive Cancer Network (NCCN) SLN algorithm. Results: 372 endometrial cancer patients were analyzed. 230 patients (61.8%) had endometrioid grade 1 or 2 tumors with <50% myometrial invasion (strategy A), and in 123 (53.4%) of these patients the tumor diameter was ≤2 cm (strategy B); 8 (3.5%) of the 230 cases had lymphatic metastasis. None of them were detected by side-specific pelvic lymphadenectomy and metastases were limited to SLNs in 7 patients. At least one pelvic side was not mapped in 107 (28.8%) cases in the entire cohort, and all of these cases would require a side-specific pelvic lymphadenectomy based on the NCCN SLN algorithm. This rate could have been significantly decreased to 11.8% and 19.4% by applying reflex frozen section examination of the uterus using strategy A and strategy B, respectively. Conclusion: Reflex frozen section examination of the uterus can be a feasible option to decide whether side-specific pelvic lymphadenectomy is necessary for all the patients who failed to map with an SLN algorithm. If low-risk factors are found on frozen section examination, side-specific pelvic lymphadenectomy can be omitted without compromising diagnostic efficacy for lymphatic spread.